Some characteristics of European (flexible) labour markets - Ignjatović, Miroljub (Družboslovne razprave, 2000)
In this article, the author analyses the structure of the European labor market(s) and the correlation between the welfare state regimes and the types of labor markets in Europe. Using the data from the Labor Force Surveys and cluster analysis as a statistical tool, the author gets slightly different picture of European labor markets from those proposed by some other authors. The cluster analysis revealed 4 distinctive, regionally structured and coherent clusters (groups) of labor markets, which could be ranked from a more traditional, industrial type to the modern, flexible type of the labor market. Similar structure, with even greater regional coherence, is found regarding the characteristics of the labor market flexibility. It is argued that for such results cultural as well as economic factors, that are hidden behind the notion of welfare state regimes, are responsible.
Keywords: European Union; Evropska unija; Evropa; Europe; zaposlovanje; delovna sila; trg delovne sile; država blaginje; družbena diferenciacija